Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/jb.00170-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CtrA Pathway in Magnetospirillum Reveals an Ancestral Role in Motility in Alphaproteobacteria

Abstract: Developmental events across the prokaryotic life cycle are highly regulated at the transcriptional and posttranslational levels. Key elements of a few regulatory networks are conserved among phylogenetic groups of bacteria, although the features controlled by these conserved systems are as diverse as the organisms encoding them. In this work, we probed the role of the CtrA regulatory network, conserved throughout the Alphaproteobacteria, in the magnetotactic bacterium Magnetospirillum magneticum strain AMB-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 58 publications
0
56
0
1
Order By: Relevance
“…About 50% of cells that tethered . Deletion of cheOp1 reduced swim ring size to the level of a non-motile DctrA mutant, which lacks any flagella filaments similar as described previously 56 . Cis-complementation of the DcheOp1 mutant strain (DcheOp1 þ ) restored WT-like behaviour.…”
Section: Resultsmentioning
confidence: 92%
“…About 50% of cells that tethered . Deletion of cheOp1 reduced swim ring size to the level of a non-motile DctrA mutant, which lacks any flagella filaments similar as described previously 56 . Cis-complementation of the DcheOp1 mutant strain (DcheOp1 þ ) restored WT-like behaviour.…”
Section: Resultsmentioning
confidence: 92%
“…The regulation of motility and flagellum biosynthesis by CtrA is posited to be an ancestral trait (21); thus, our observation of CtrA-binding sites upstream of genes involved in motility and chemotaxis is to be expected. Remarkably, in P. hirschii, the putative mechanism of CtrA regulation of motility is more similar to that of C. crescentus than to that of S. meliloti.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, genes shown to be essential for cell cycle progression in C. crescentus have also been shown to have important functions in cell cycle regulation of Agrobacterium tumefaciens (9)(10)(11)(12), Sinorhizobium meliloti (3,(13)(14)(15)(16), and Brucella abortus (14,(17)(18)(19)(20). Notably, the essentiality and regulons of cell cycle regulators are varied in Alphaproteobacteria, suggesting that mechanisms of cell cycle regulation are plastic and may provide a means of adapting to a particular environment (12,15,21).…”
mentioning
confidence: 99%
“…For some species of this bacterial group, it has been reported that CtrA does not control the cell cycle, but it controls directly or indirectly the expression of the flagellar genes (14)(15)(16)(17)(18)(19). In this group of bacteria, there is no evidence regarding the control of the activity of CckA, but it has been reported that the expression of cckA, chpT, and/or ctrA is reduced in quorum sensing mutants in Ruegeria sp.…”
mentioning
confidence: 93%